Implementation of Entrepreneurship Education to Increase Student Entrepreneurship Interest - Aqila Fikhia; Hartin Kurniawati; Agung Perwira; Azizah Nurasna (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Entrepreneurship education not only presents theoretical basics regarding the concept of entrepreneurship, but is also able to shape students' way of thinking, behavior and views regarding entrepreneurship. This research aims to clarify the concept of entrepreneurship education, how to apply entrepreneurship education in lectures to increase students' interest in entrepreneurship, as well as the impact of entrepreneurship lectures on students. This research is a type of qualitative research, a research process that produces written or verbal descriptive data regarding the behavior of people being observed. Qualitative research usually involves an in-depth and detailed investigation of a phenomenon, with clear and detailed data. Inductive analysis is used to discover the true meaning of the phenomena studied. The results of this research have a positive impact on students by developing entrepreneurial skills, such as financial management and marketing. They learn how to run and manage a business to become valuable capital for future careers. Being involved in trading gives students practical, real-world experience that cannot always be obtained in the classroom. Trading activities can improve students' soft skills, such as communication, leadership, teamwork and time management.